Human rights big data and technology: digital policing and human rights, 2023 - McGregor, Lorna (UK Data Service, 2024)
The main project aims were to examine the human rights implications of rapidly developing technologies. As noted above, in an increasingly digitised world, technological developments and the collection, storage and use of 'big data' pose unprecedented challenges for the protection of human rights. The aim of the project was to examine the intersection of such technological developments and the ideals of human rights protection. The work focused on both positive and negative aspects of this relationship. As noted above, the core research aims were organised on these issues that cut across the threats and opportunities:1) How is the use of ICT and big data shaping the content and scope of rights? (2) How does the use of ICT and big data shape operational practices across state and non-state activities? What new theoretical questions and implications for human rights are generated? (3) What methodologies are needed to identify and document the misuse of modern technologies and the failure to comply with rights-based obligations? (4) How can the use of ICT and big data best support evidence-based approaches to human rights protection and advocacy? (5) What possibilities and limitations exist for regulating the collection, storage and use of ICT and big data by states and non-state actors? The deposited data largely focuses on interviews with law enforcement and security agency representatives about uses of digital technology. We found that an enthusiastic embrace of technnology often existed yet this was not always accompanied by the development of codes of practice, regulatory frameworks and operational guidence on how they should be used. In addition to a potential regulatory vacuum, such disconnects also placed additional burdens on law enforcement themselves as they sought to apply existing rules and regulations. This is something we have described in publications as 'surveillance arbitration'. We also include interviews with civil society actors and lawyers that interrogate these issues and associated digital rights campaigning matters in more detail. Edward Snowden's leaks about the extent of US and UK intelligence services' electronic surveillance dramatically demonstrated how in an increasingly digitised world, technological developments and the collection, storage and use of 'big data' pose unprecedented challenges for the protection of human rights. The aim of this programme of research is to ensure that the use of technological developments and big data are compatible with the ideals of human rights protection and can even have a positive impact. Snowden's revelations are part of a much bigger picture in which electronic monitoring and data is collected and shared by companies and states on a routine, daily basis through social media, consumer activity and smartphones. The same technologies that threaten our privacy also provide opportunities for enhanced protection of human rights through better documentation of human rights violations and by demonstrating the effectiveness of rights-shaped policies in order to influence resource allocation and budgets. Existing work either fails to consider the rights-implications of the use of Information and Communication Technology (ICT) and big data or focuses on a particular right. What is missing is a wider investigation into the diverse and complex rights-implications (positive and negative) of the use of ICT and big data including, but not limited to, privacy and the many social, ethical and legal issues lurking beneath the surface of human-machine interaction and use of big data. Moreover, regulation of the use of ICT and big data is currently fragmented between states, the United Nations and internet governance sector. This project will provide added value by offering a fuller picture of the totality of human rights issues raised by ICT and big data to advance new thinking and regulatory solutions. The research questions focus on issues that cut across the threats and opportunities:1) How is the use of ICT and big data shaping the content and scope of rights? (2) How does the use of ICT and big data shape operational practices across state and non-state activities? What new theoretical questions and implications for human rights are generated? (3) What methodologies are needed to identify and document the misuse of modern technologies and the failure to comply with rights-based obligations? (4) How can the use of ICT and big data best support evidence-based approaches to human rights protection and advocacy? (5) What possibilities and limitations exist for regulating the collection, storage and use of ICT and big data by states and non-state actors? The project will be organised into 4 work streams. The first (WS1) will focus on the overarching and synthesising themes. This will be complemented and informed by three in-depth studies: state and non-state surveillance (WS2); health as an example of using new technologies and big data for accountability purposes and evidence-based approaches to rights (WS3); and human rights advocacy and humanitarian work (WS4). The project will use multiple methods (desk research, interviews, econometrics, comparative case studies and computational techniques). Communication and impact streams will be developed across the different stakeholder communities to establish agreement and a shared vocabulary by forming an expert working group of practitioners (human rights and technology), international internet governance, UN actors and academics that will meet twice a year to develop international standards on information technology, big data and human rights. Dissemination and engagement with academics, practitioners and the public will be achieved via an interactive website; social media channels; conferences; public events; academic publications; shorter practice-orientated articles, policy briefings and blogs; media pieces; and time sensitive interventions targeting key policymakers and influencers and international, regional and national courts.